Organic Memory Devices 2D Mica Crystal as Electret in Organic Field-Effect Transistors for Multistate Memory (Adv. Mater. 19/2016) - Zhang, Xiaotao (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.